The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1590/s0021-75572003000300009
|View full text |Cite
|
Sign up to set email alerts
|

Tratamento de manutenção da asma persistente à admissão em ambulatório de pneumologia pediátrica

Abstract: the rate of inhaled corticosteroid therapy was higher than that found in Brazilian studies and it is comparable to the results of some international studies. A decrease in the use of oral corticosteroids was also observed. Both findings may be related to the implementation of an asthma program in the public health system of Belo Horizonte, which began in 1996.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
2
0
4
Order By: Relevance
“…Observou-se, no presente estudo, que os percentuais de atendimento de urgência encontrados nas duas USF estudadas sem programa consolidado foram ainda menores do que os observados por Camargos & Profeta 16 em Belo Horizonte (Minas Gerais), onde 92,7% das crianças de 4 a 14 anos haviam Tabela 4 Prevalência de atendimentos de urgência devidos à asma segundo faixa etária dos asmáticos cadastrados em unidades de saúde da família (USF) com programa consolidado e não consolidado e respectivas razões de prevalência (RP) e intervalo de 95% de confi ança (IC95%). Londrina, Paraná, Brasil, 2007. procurado atendimento em serviços de urgência em um período de doze meses anteriores à admissão em ambulatório de pneumologia.…”
Section: Discussionunclassified
“…Observou-se, no presente estudo, que os percentuais de atendimento de urgência encontrados nas duas USF estudadas sem programa consolidado foram ainda menores do que os observados por Camargos & Profeta 16 em Belo Horizonte (Minas Gerais), onde 92,7% das crianças de 4 a 14 anos haviam Tabela 4 Prevalência de atendimentos de urgência devidos à asma segundo faixa etária dos asmáticos cadastrados em unidades de saúde da família (USF) com programa consolidado e não consolidado e respectivas razões de prevalência (RP) e intervalo de 95% de confi ança (IC95%). Londrina, Paraná, Brasil, 2007. procurado atendimento em serviços de urgência em um período de doze meses anteriores à admissão em ambulatório de pneumologia.…”
Section: Discussionunclassified
“…O impacto do uso do corticoide na redução da morbimortalidade da asma foi evidenciado em vários estudos 8,9,10,11 . A prevalência, a gravidade do quadro e a conduta médica adotada na comunidade em estudo vão influenciar as taxas de hospitalização por asma 12 .…”
Section: Introductionunclassified
“…Inhaled corticosteroids, the main pharmacological choice for control of this disease, were reported to have been used by only one child in this population. Other studies conducted in Brazil, although focused on children cared for in health units, found frequencies of use of inhaled corticosteroids between 2 and 6% [18, 29]. …”
Section: Discussionmentioning
confidence: 99%
“…Rosário Filho reported an increase in spending on drugs for asthma treatment and in hospitalizations due to this disease [16]. Other studies performed in children with asthma in the public health care facilities in Brazil revealed small proportions of use of anti-inflammatory treatment, ranging from 6.0 to 14.0% [17, 18]. In Brazil, the lack of population-based studies on the use of anti-asthmatics in children, as well as on the reasons for this lack, necessitates such studies, particularly as the use of these drugs is considered an indirect indicator of quality of care provided to asthmatic children.…”
Section: Introductionmentioning
confidence: 99%